Pelaksanaan Safety Drill Sesuai Aturan SOLAS Chapter III di KM Kendagha Nusantara 03 - Junior Ante Sulu; Yeddy T.Th. Ombuh; Aliong Silalahi (Journal of Nautical Science and Technology, 2025)
For ship operations, the crew must prioritize safety due to its impact on human lives. This research aims to evaluate the implementation of safety drills in accordance with SOLAS CHAPTER III on KM KENDAGHA NUSANTARA 03. The author uses a participatory observation method, directly engaging in activities to collect data. The observation results indicate that the ship’s crew is not yet prepared for emergency situations; they are unfamiliar with safety equipment and emergency procedures. Additionally, the lack of attention to safety equipment maintenance makes drills less effective, potentially endangering the crew’s lives. Although the safety drills have been conducted according to SOLAS regulations, there are still deficiencies in the crew’s understanding of procedures and equipment maintenance. Crew awareness of their duties and responsibilities in executing safety drills is crucial for improving safety on the ship.